P426 Health-Related Quality of Life and Work Productivity in patients with moderate-to-severe Inflammatory Bowel Disease in Argentina: Data from the RISE AR study. (27th May 2021) - Correa, G J; Yantorno, M; Olivera Sendra, P; Lasa, J S; Lubrano, P; Balderramo, D C; Zubiaurre, I; Ruffinengo, O; Brion, L; Leonardi, D B; El-Hakeh, J; Guimaraens, P N; et al.
Abstract: Background: Patient-reported outcomes (PROs) are increasingly recognized as complementary to objective markers of disease activity, yet evidence on PROs in inflammatory bowel disease (IBD) in the real-world setting in Latin America is limited. Herein, we describe health-related quality of life (HRQoL) and work productivity and activity impairment (WPAI) of IBD patients (pts) in Argentina. Methods: RISE-AR (NCT03488030) was a non-interventional study with a cross-sectional evaluation and a 3-year retrospective chart review conducted in 7 centres in Argentina (12/2018-05/2019) to assess healthcare resource utilisation, HRQoL and WPAI. Adult pts (≥18 yr old) with a previous diagnosis of moderate-to-severe (Mod/Sev) ulcerative colitis (UC) or Crohn′s disease (CD) based on clinical, endoscopic or imaging criteria ≥6 months prior to enrolment, were included. HRQoL (IBD Questionnaire [IBDQ], 5-dimensional EuroQoL measure [EQ5D]) and WPAI instruments were administered at screening. Disease activity at enrolment was classified as Mod/Sev (Harvey Bradshaw Index ≥8 or partial Mayo Score ≥5) vs. "no-or-mild" (No/Mild). A p-value ≤0.05 was considered statistically significant (Mann-Whitney U test). Results: Overall, 246 pts were included (41.1% CD; 58.9% UC). At enrolment, median (range) age (years) was 39.5 (18.2-74.0) for CD (51.2% female) and 41.9 (18.0-80.4) for UC (55.2% female) pts; 20 pts (9.3% CD; 7.7% UC; excluding 4 ostomized pts) had Mod/Sev disease activity. During the previous 3 years, 17.8% (CD) and 1.4% (UC) of pts required ≥1 surgery, and 33.7% (CD) and 21.4% (UC) were hospitalized. No/Mild pts showed significantly higher overall HRQoL scores (mean±SD) vs. Mod/Sev pts in CD (IBDQ: 178.1±35.4 vs. 140.0±43.5, p<0.05; EQ5D [visual analogue scale]: 75.7±1.8 vs. 64.4±5.5, p<0.05) and UC (180.2±32.9 vs. 132.9±43.8, p<0.001; 77.1±1.3 vs. 57.7±5.3, p<0.001), respectively. Activity impairment was reported by 55.4% and 58.6% of CD and UC pts, respectively, while 37.9% and 43.9% of CD and UC employed pts (67 CD, 92 UC; Mod/Sev: 5 CD, 6 UC) reported work impairment. Mod/Sev IBD pts had higher absenteeism (30.8% vs. 6.3%, p<0.05) and presenteeism (20.0% vs. 7.5%, p=0.149) vs. No/Mild pts. Female gender, surgeries and hospitalizations were associated with lower QoL in the overall IBD population. Conclusion: This is the first study to evaluate QoL and WPAI in IBD pts in Argentina. Pts with Mod/Sev activity showed impaired QoL and WPAI compared to No/Mild pts. Whilst, less than 10% of IBD pts had Mod/Sev disease activity at enrolment, nearly 60% of the overall IBD population reported either work or activity impairment. Thus, disease activity scores alone may fail to assess the real burden of IBD, suggesting a relevant role for PROs in disease management.